The role of social media in emotional communication among individuals in their third age - Đumić, Tihana (Teorija in praksa, 2024)
The study focused on investigating and analysing the perception of Facebook’s role, as one of the components in the field of Information and Communication Technologies (ICT), namely, social media, on the quality of emotional interaction, particularly among individuals in their third age. The research sample comprised 260 participants of various ages, divided into two age groups – under 50 and over 50 years old. Participants’ opinions were obtained through empirical research, employing quantitative methods and surveys as the research technique. The research findings indicate that age influences participants’ attitudes to digital communication as a means and medium of emotional communication in various contexts. Participants in the third age exhibit stronger reservations towards Facebook as a tool for emotional communication and are more cautious about the use of modern communication methods offered by new social media techniques. They are also less inclined to abandon traditional interpersonal interactions. The results reveal general distrust in the information circulating on Facebook and underscore the advantage of maintaining each interpersonal communication, encompassing all elements of emotional relationships beyond the realm of the Internet, or the information mediation services offered by ICT, primarily social media.
Keywords: alienation; čustvena komunikacija; emotional communication; Facebook; informacijske in komunikacijske tehnologije; information and communication technologies; odtujenost; third age; tretje življenjsko obdobje